Interfollicular Hodgkin’s Lymphoma - A Diagnostic Dilemma - Zeeba, S; Safia, R; Pradeep, SC; Shruti, S; Sujala, K (Bangladesh Journal of Medical Science, 2012)
Interfollicular Hodgkin's lymphoma represents an unusual pattern of focal involvement of interfollicular zones by Hodgkin's lymphoma along with florid reactive follicular hyperplasia. It is often mistakenly diagnosed as a reactive change. We report a case of a 36 years old male with persistent lymphadenitis for three years, who was finally diagnosed as Interfollicular Hodgkin's lymphoma after being incorrectly diagnosed as reactive lymphadenitis. This case is reported in view of the unusual pattern of Hodgkin's lymphoma as well as its misdiagnosis as a benign lesion. DOI: http://dx.doi.org/10.3329/bjms.v11i3.11739 Bangladesh Journal of Medical Science Vol. 11 No. 03 July12